Human Capital Pricing Equations with an Application to Estimating the Effect of Schooling Quality on Earnings - Heckman, James; Layne-Farrar, Anne; Todd, Petra (The Review of Economics and Statistics, 1996)
James Heckman, Anne Layne-Farrar, Petra Todd, Human Capital Pricing Equations with an Application to Estimating the Effect of Schooling Quality on Earnings, The Review of Economics and Statistics, Vol. 78, No. 4 (Nov., 1996), pp. 562-610